2022
DOI: 10.3389/fmmed.2022.970744
|View full text |Cite
|
Sign up to set email alerts
|

The vascular protective effect of matrix Gla protein during kidney injury

Abstract: Matrix Gla protein (MGP) is a small secreted protein and requires vitamin K dependent γ-carboxylation for its function. MGP has been identified as a local inhibitor of vascular calcification because MGP-deficient mice die due to severe arterial calcification and resulting arterial rupture. Clinical trials revealed that reduction in active MGP predicts poor prognosis in patients due to cardiovascular complications. However, recent studies showed that MGP controls angiogenesis during development. MGP-deficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…EOM genes unique to the quiescent state included Tshr, encoding the thyroid-stimulating hormone receptor, which has been previously identified in bulk RNAseq as "EOM-resistant" kept upon engraftment into the limb (Evano et al, 2020b), and shown to control senescence in MuSCs of DMD rats (Taglietti et al, 2023). Matrix Gla protein (Mgp), which is a critical regulator of angiogenesis in multiple organs (Kida and Yamaguchi, 2022), was identified as exclusively upregulated in EOM cells upon activation (Figure 3H). Amongst the conserved EOM genes across cell states we identified Pitx2, a well-known major upstream regulator of EOM development (Gage et al, 1999b), Fos gene family members (Fos and Fosb), with Fos being recently identified in a subset of limb MuSCs with enhanced regenerative capacity (Almada et al, 2021), and Igfbp7, a specific marker of quiescent MuSCs that is downregulated upon activation (Fukada et al, 2007) but also reported to be upregulated in MuSCs upon exercise (Chen et al, 2020) (Figure 3F, Suppl Figure 3B, C).…”
Section: Eom and Ta Muscs Retain Distinct Molecular Signatures After ...mentioning
confidence: 99%
“…EOM genes unique to the quiescent state included Tshr, encoding the thyroid-stimulating hormone receptor, which has been previously identified in bulk RNAseq as "EOM-resistant" kept upon engraftment into the limb (Evano et al, 2020b), and shown to control senescence in MuSCs of DMD rats (Taglietti et al, 2023). Matrix Gla protein (Mgp), which is a critical regulator of angiogenesis in multiple organs (Kida and Yamaguchi, 2022), was identified as exclusively upregulated in EOM cells upon activation (Figure 3H). Amongst the conserved EOM genes across cell states we identified Pitx2, a well-known major upstream regulator of EOM development (Gage et al, 1999b), Fos gene family members (Fos and Fosb), with Fos being recently identified in a subset of limb MuSCs with enhanced regenerative capacity (Almada et al, 2021), and Igfbp7, a specific marker of quiescent MuSCs that is downregulated upon activation (Fukada et al, 2007) but also reported to be upregulated in MuSCs upon exercise (Chen et al, 2020) (Figure 3F, Suppl Figure 3B, C).…”
Section: Eom and Ta Muscs Retain Distinct Molecular Signatures After ...mentioning
confidence: 99%